Comparing Explicit And Implicit Feedback Techniques For Web Retrieval: TREC-10 Interactive Track Report - White, Ryen W.; Jose, Joemon M .; Ruthven, I. (Text REtrieval Conference - 10 (TREC 2001) Gaithersburg, Maryland, U.S.A, 2001)
In this paper we examine the extent to which implicit feedback (where the system attempts to estimate what the user may be interested in) can act as a substitute for explicit feedback (where searchers explicitly mark documents relevant). Therefore, we attempt to side-step the problem of getting users to explicitly mark documents relevant by making predictions on relevance through analysing the user’s interaction with the system. Specifically, we hypothesised that implicit and explicit feedback were interchangeable as sources of relevance information for relevance feedback. Through developing a system that utilised each type of feedback we were able to compare the two approaches in terms of search effectiveness.